Analisis komposisi dan struktur vegetasi terhadap upaya konservasi burung cenderawasih di Kampung Nij Kabupaten Manokwari Selatan - C. E. Matakupan, Dessy; Holle, Yolanda; Moeljono, Soetjipto (Cassowary, 2025)
ABSTRACT: Vegetation composition and structure are important parameters in conservation birds of paradise. This research aims to provide base data on the composition and structure of vegetation of the bird of paradise habitat to support ecotourism observing birds of paradise in Nij Village. The vegetation sampling method uses a combination of stripes and grid lines. Vegetation analysis to obtain vegetation composition and structure, important value index, Margalef species richness index (Dmg), Shannon-Wiener diversity index (H') and evenness index (E). Describe the types of trees used by birds of paradise as places to eat, play, rest, mate, sleep and nest. The research results obtained 15 plots with a total number of 107 species belonging to 44 families with 514 individuals. The horizontal vegetation structure forms an inverted "J" curve with the highest density at the seedling growth stage and the lowest at the tree growth stage. Species dominance trees Dillenia papuana, poles Dillenia papuana, saplings Artocarpus altilis and Diospyros papuana seedlings. The diversity index value is very high with a diversity value (H') above 3%, richness index (Dmg) above 4% and evenness (E) in the range of 0.81%-0.90%. There are two conservation measures in protecting the bird of paradise habitat, namely protecting the forest as a sacred area and prohibiting land clearing around the bird of paradise habitat.